Effects of medium-chain fatty acid diets on nursery pig performance - Druecker, Logan J.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
Feed additives like carbadox and Zinc oxide are used in pig production to improve performance and act as antimicrobial agents. However, drawbacks include building antibiotic resistance and environment pollution respectively. It is important to research alternative additives that could replace these compounds and eliminate the drawbacks while still improving performance. A study at the KSU Swine Unit used 360 weanling pigs (DNA 200*400; 5.4±0.2 kg) to analyze the effects of MCFA on nursery pig performance. Treatments included; 1) control 2) ZnO 3,000 ppm in Phase 1 and 1,500 ppm in Phase 2 3) carbadox 50 g/ton 4) 1% Feed Energy R2 (Feed Energy Corp., Des Moines, IA) 5) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany) 6) 1% C6, C8, C10. The treatments were tested for 35 days using 10 replicates/treatment in a completely randomized design with the pens being the experimental unit and an alpha-value of P<.05. Weekly recordings were collected of pig weights and feed disappearance. Treatment diets were fed from d 0 to 19 with d 20 to 35 being a common phase. During the overall treatment, pigs fed ZnO had improved (P<0.05) ADG and ADFI than those fed the control, MCFA, and R2 diets. Furthermore, pigs fed carbadox had improved (P<0.0001) ADG compared the control and R2 diets. There was no statistical difference between any of the treatments regarding the G:F. Overall (d 0 to 35), the only statistical differences between the treatments were that ZnO had improved (P=0.012) ADG than R2 and that both ZnO and Carbadox improved (P=0.001) ADFI than R2. While diets with carbadox or ZnO had the better overall performance, the results of this study suggest that nursery pigs fed diets with MCFA may have improved growth performance.
Keywords: Spring 2019